FLOATING BRIDGE - BALINGAL KOMAL VITTAL; VADNAL AARTI SHRINIWAS; KODAM PALLAVI VYANKATESH (International Journal of Innovations in Engineering Research and Technology, 2021)
Very largefloating structures (VLFS) have attracted the attention of architects, city planners and because they provide an exciting environmentally friendly solution for land creation from sea has opposed to the traditional land reclamation method . The application of VLFS as a floating piers , floating hotels ,floating fuel storage facilities, floating stadia ,floating bridges, floating airports, and even floating cities have trigged extensive research studies in the past two decades. The VLFS technology has developed considerably and there are many innovative methods proposed to minimize the hydro elastic motion, improve the mooring system and structural integrity of the VLFS. Large-scale floating structures are one solution to satisfy the demand for space by utilizing the ocean.